GAMBARAN SISTEM DISTRIBUSI UNIT DOSE DISPENSING (UDD) TERHADAP RETUR OBAT INJEKSI GENERIK DI INSTALASI FARMASI RAWAT INAP SALAH SATU RUMAH SAKIT SWASTA DI KOTA BANDUNG - Eva Kusumahati; Dea Anita; Monika Patrisia (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Drug returns are one of the jobs in inpatient pharmacy services. The use of an inappropriate distribution system can lead to high drug returns. Objective: to find out the description of the use of the UDD distribution system for generic injection drug returns in one of the inpatient pharmacy installations in the city of Bandung. Observational method with retrospective data collection technique in which data were collected using a UDD individual prescription distribution system. Results: indicates that generic injection drugs are drugs with the highest number of returns. The comparison of the percentage of drug returns before and after the UDD distribution system, namely Ceftriaxone was 3.95% and decreased to 3.61%, Citicoline 9.72% decreased to 5.17%, Dexamethasone was 5.20% down to 3.77%, Ketorolac 11.19% down to 11.14%, Omeprazole 6.55% to 4.23%, Ondansetron 4 mg 5.52% to 4.79%, Ondansetron 8 mg by 8.84% to 5.04%, Pantoprazole 8.09% to 6.47%, Ranitidine by 4.86% to 2.72% and Tranexamic Acid 250 by 20.97% to 4.39 % Conclusion: there is a decrease in the percentage of injection drug returns in hospitalized patients.